Orbit based procedure for doublets of scalar fields and the emergence of triple kinks and other defects - Brito, G. P. de [UNESP]; Dutra, A. de Souza [UNESP] (Elsevier B.V., 2014)
In this work we offer an approach to enlarge the number of exactly solvable models with two real scalar fields in (1 + 1)D. We build some new two-field models, and obtain their exact orbits and exact or numerical field configurations. It is noteworthy that a model presenting triple-kinks and double-flat-top lumps is among those new models. (C) 2014 The Authors. Published by Elsevier B.V.